2019
DOI: 10.1038/s41390-019-0709-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular evidence of accelerated ageing following very preterm birth

Abstract: BackgroundThe mechanisms responsible for the associations between very preterm birth and a higher risk of poor cardiovascular and metabolic health in adult life are unknown. MethodsComparison of the clinical and molecular phenotypes of healthy, normal weight young adults (18-27 years), born very preterm (<33 weeks gestational age (GA)) and at full-term (37-42 weeks GA).Outcomes included whole body magnetic resonance imaging; hepatic and muscle 1 H magnetic resonance spectroscopy; blood pressure (BP) measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
(40 reference statements)
0
19
0
3
Order By: Relevance
“…Additionally, we found that liver fat was associated with lower birth weight (p=1.76e-30, beta = −0.0849) and comparative body size at age 10 (p=4.79e-76, beta = −0.22). Low birth weight has previously been associated with severity of pediatric non-alcoholic steatohepatitis (NASH) ( Bugianesi et al, 2017 ), abnormal fat distribution ( Parkinson et al, 2020 ), and liver fat levels in adults born prematurely ( Thomas et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we found that liver fat was associated with lower birth weight (p=1.76e-30, beta = −0.0849) and comparative body size at age 10 (p=4.79e-76, beta = −0.22). Low birth weight has previously been associated with severity of pediatric non-alcoholic steatohepatitis (NASH) ( Bugianesi et al, 2017 ), abnormal fat distribution ( Parkinson et al, 2020 ), and liver fat levels in adults born prematurely ( Thomas et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effects are substantial. Children born too soon, too small, or to a mother who is underweight, overweight, or has diabetes are 1.5-6 times more likely to develop NCD than those born full term with a healthy birthweight or to a healthy mother 3. Globally, preterm birth rates range from 5-15% and are rising, around 10% of full term babies are growth restricted, and in many countries, 50% of pregnant women are overweight or obese 4.…”
Section: Follow the Sciencementioning
confidence: 99%
“…Neena Modi , 1 Gabriella Conti, 2 Mark Hanson 3 Twenty-first century science underpinned the rapid global response to COVID-19, identifying the causal pathogen, sequencing the SARS-CoV-2 genome, developing vaccines and initiating clinical trials, within 9 months of first appearance. Although in tackling the immediate consequences of the pandemic countries responded to science in different ways, every nation now grapples with the economic consequences and the question of where to focus investment.…”
Section: Viewpointmentioning
confidence: 99%
“…1 For example, babies born preterm, are growth restricted or born to mothers who are undernourished, overweight or with diabetes represent a large and growing proportion of all births and are at substantially increased odds of developing hypertension, diabetes, renal impairment, heart disease and other chronic NCDs in adult life. 2 In highincome countries, around two-thirds of adults are now overweight or obese. Preterm births are rising, with an estimated global rate of 10.6% in 2014.…”
Section: Viewpointmentioning
confidence: 99%